THE EFFECT OF MARDI WIYATA FOUNDATION GOVERNANCE ON PUBLIC TRUST WITH FINANCIAL PERFORMANCE - Klemens Mere (Enrichment : Journal of Management, 2022)
The main objective of this study is to determine the governance of the Foundation (transparency and accountability) to public trust simultaneously, partially with fiscal performance as a moderating variable, the effectiveness of non-program activities as a moderating variable, public support as a moderating variable, investment performance as a moderating variable, and program activities as moderating variables. The research method used is quantitative research with the research subjects are donors who have donated to the Mardi Wiyata Foundation for more than 5 years and parents of students at the Mardi Wiyata Foundation. Main Findings: Transparency and accountability variables simultaneously have a significant positive effect on public trust. Partial transparency variables have a significant positive effect on public trust, while the Theory and Policy Implications is the existence of transparency and accountability to public trust simultaneously. There is partial transparency and accountability for public trust. This research bridges the foundation's governance to public trust through financial performance.